European Ice Sheet Modelling Initiative (EISMINT) model intercomparison experiments with first-order mechanics - Saito, Fuyuki; Abe-Ouchi, Ayako; Blatter, Heinz (Journal of Geophysical Research: Earth Surface, 2006)
ISSN:0022-1406 ISSN:0148-0227 ISSN:0196-6928 ISSN:0196-6936 ISSN:2156-2202